Kebidupan SosiaJ Ekonomi NeJayan Ikan Kering di Kenagarian Pasir Ganting Kecamatan Pancung Soal Kabupaten Pesisir Selatan (1990-2012)."Skripsi. Program Studi Pendidikan Sejarah. STKIP - Naldi, Refre - (Pendidikan Sejarah, 2014)
Fishermen are people who live off the livelihood of marine products. In Indonesia, the fishermen usually dwelt on the outskirts of the beach or the ocean as well as coastal fishin g communities District of beheading Problem Ganting sand has long been dependent on the sea. Most of them live on dried fish processing business. Based on the phenomenon of the problem is formulated as follows: I. How dry fish processing business carried on fishing Sand Ganting District of beheading Problem South Coastal District of years I990 - 20 12? 2. How is the socio economic life of the fishing community after pursue the dry fish processing in Nagari Sand Ganting Problem beheaded Subdistrict South Coastal District? The purpose of this study was to see dried fish processing business in Kenagarian Sand Ganting, and changes in socio-economic change in the lives of the fishermen dried fish processing business is. This study uses historical research consists of the following four stages: (1). Heuristics, which collects a variety of information, either through written sources, as well as field interviews, (2). Source criticism is an activity to test the validity of the research data through external criticism and internal ciiticism, (3).   Interpretation,   ie,  activity   interpret   data,  and   analyzing  the  data  obtained,   and   (4).Historiography as lanmgkab tertakhir that tries to present the research  results in the form of a thesis. The results showed that the dried fish processing business starts intensively by fishermen Sand Ganting since the 1990s industry in the form of household (family), in which almost all the family members involved. Since 1990 the business development is quite rapid, evident from the increasing productioo and marketing area expanded . In the meantime, social and economic life of fishermen also increased. This is evident from the increase in their income from year to year, in addition to an increase in the education of children of fishermen , health level is getting better, which is accompanied by a more decent housing conditions, and lifestyle changes are more consumptive. Based on the research that has been done can disirnpulakan that, fishermen dried fish in Nagari Sand Ganting subdistrict beheaded Problem has been able to bring changes to the social and economic life, in comparison to the previous year.